PELINDUNGAN HAK EKONOMI KARYAWAN INVENTOR ATAS PATEN YANG DIHASILKAN DARI HUBUNGAN KERJA - Marwandy, Irsyad; Rafianti , Laina; Suryamah, Aam (DAS Institute, 2024)
Employees who are inventors often collaborate with employers to secure funding and facilities for patent research and development. In response to this development, the government established the Patent Law to protect the patent rights of employee inventors for patents resulting from their employment relationship. This study is a normative-sociological legal research. The aim of this research is to find the appropriate mechanism for creating a compensation agreement and fair and reasonable compensation standard for employee inventors. The subjects of this research are employee inventors and employers. The data collection method in this study are literature review and interviews. The data includes regulations, legal experts' opinions, dictionaries, encyclopedias, and others. Based on this research, it was found that there is uncertainty regarding the bargaining position of employee inventors in the agreement drafting process and the standards for providing compensation to employee inventors for the patents they produce. Therefore, a strong legal system is needed to regulate the forms and values of compensation which meet fair and reasonable standards to ensure legal certainty for employee inventors.